Indian Rituals and Herbal Remedies: A Hope Against Corona Pandemic - Srivastava, Astha; Pandey, Brijesh Kumar; Mishra, Vipin; Dikshit, Anupam; Shukla, Shashi Kant (Indian Forester, 2020)
World health organization (WHO) starts investigating the possibilities in Phyto-medicines after the outburst of SARS in 2002-2003. In the continuation of viral pandemics in December 2019, a novel corona virus came into existence. The whole world is facing the severe condition due to outbreaks of the present virus. More than two lakhs persons have lost their lives, livelihood and economy due to this COVID-19 virus. In the present review authors are trying to establish the relationship between viral disease and herbal secondary metabolites and rituals smoke with special context to India. Human beings are inhaling the ceremonial fumes from the primeval period. Several plants have shown their antiviral properties against the COVID family viruses such as Ocimum tenuiflorum L.Even every civilization has its strong folk remedial knowledge based on plants, animals and natural products. The ritual vapours not only purify the environment but also increases the immunity of a person. Other promising cure to break the spreading chain of this virus is lockdown. When the whole world is in search of effective medicine for the catastrophic disease, the prospects of Ayurveda should be explored.